Study on Effect of Fibrolytic Enzymes Supplementation on in vitro Gas Production Kinetics and Ruminal Fermentation of Date Palm (Phoenix dactylifera) By-Products - Khalil Abid; Jihene Jabri; Yves Beckers; Hela Yaich; Atef Malek; Jamel Rekhis; Mohamed Kamoun (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
This study was conducted in order to assess the influence of four doses (0, 0.5, 1, and 2 mg (g dry matter)-1 of commercial fibrolytic enzymes (MAXFIBER-I®, SHAUMANN GmbH, Wahlstedt, Germany) on in vitro fermentation of date palm (Phoenix dactylifera) by-products: date kernels, wasted dates, floral stems, and palm fronds. Rumen contents were obtained from two non-lactating Holstein cows. Enzyme supplementation to by-products was carried out 12 h prior to incubation. Compared to the control, the enzymatic supplementation quadratically increased the extent but not the gas production rate of date kernel fermentation. Indeed, the potential gas production increased notably by 14.8% with the lowest enzymes dose following recorded gas production after 48, 72, and 96 h of incubation. The estimated organic-matter digestibility, metabolisable energy, and total volatile fatty acids in the incubation fluid tended to be increased with the lowest dose by 7.8%, 8.4%, and 13.9% respectively. For the wasted dates, this feed additive tended to linearly increase the gas production rate of fermentation with the highest dose. On the other hand, this supplementation had no effect on the ruminal fermentation of the floral stems and palm fronds. The exogenous fibrolytic enzymes were more effective on fibrous but not on lignified date palm by-products.